2021
DOI: 10.3390/ani11113164
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Behavior around Calving on Reproduction and Wellbeing of Zebu Type Cows and Calves

Abstract: The behaviors associated with domestic cattle such as maternal care are quite similar to those behaviors observed in wild ungulates. These behaviors allow the cow to bond with her calf, protect and provide it with nourishment and ultimately reduce the bond at weaning. Although maternal behavior is an important factor influencing the survival and early development of the newborn calf, Zebu type cows around calving have not been studied extensively. Herein, we consider the four main aspects of maternal behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Stated that Body Condition Score (BCS) can have an effect on post-partum date and subsequent pregnancy rates. As reported by Orihuelaand Galina [21] changes in body reserves are the driving force for a prompt restoration of ovarian activity and pregnancy rather than the time postpartum. Maqhashu, (2016) pointed out that BCS may be used as a management tool for assessing physiological state and, is the most practical method of evaluating energy reserves.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Stated that Body Condition Score (BCS) can have an effect on post-partum date and subsequent pregnancy rates. As reported by Orihuelaand Galina [21] changes in body reserves are the driving force for a prompt restoration of ovarian activity and pregnancy rather than the time postpartum. Maqhashu, (2016) pointed out that BCS may be used as a management tool for assessing physiological state and, is the most practical method of evaluating energy reserves.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally it is understood that communal grazing animals suffer mostly from inadequate nutrition [7]. In a number of studies nutritional stress has been demonstrated to reduce resumption of ovarian cyclicity [16,20,21,32,50,60]. Furthermore an ovulation is observed in beef cows managed in pasture-based systems as they display a prolonged PPI [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several characterization studies in different parts of Latin America, it has been observed that most farmers use manual milking [ 137 ], wherein the cow is accompanied by her calf ( Figure 4 ). The calf is usually allowed to suckle on residual milk, one teat, or other combinations [ 138 ]. This facilitates the process of milk let down, but has a strong influence on the resumption of ovarian activity, where the effects of suckling, the presence of the calf, and nutritional status all participate [ 139 ].…”
Section: Breeding Proceduresmentioning
confidence: 99%
“…In beef production systems, successfully raising and nourishing a calf from birth to weaning is dependent on the success of a cow’s mothering ability [ 6 ]. The majority of calf deaths in rangeland environments such as those in North America have been found to occur within the first 24 h to 7 days of life [ 7 ].…”
Section: Introductionmentioning
confidence: 99%